Reformulasi Hierarki Peraturan pada Pembentukan Peraturan Perundang-Undangan di Indonesia - Suwardi Sagama (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2018)
This article discusses the hierarchy of regulation formation. The problem being discussed in this article is related to the regulations that are formed contrary to the rules above and therefore, they are canceled or revised. Although explicitly in the formation of regulations, it is mandatory to follow the regulation hierarchy. Hence, it causes financial problems because the regulations cannot be implemented. It is juridical normative based research. The result of this research suggests that it is necessary to reformulate the regulations hierarchy on the formation of state regulations. It also suggests that the hierarchy of the regulations formation has positive and negative values. It is positive because it can maintain orderliness in the formation of regulations, while negative values will occur in the formation of the regulations. Therefore, to strengthen the hierarchy of the formulation of laws and regulations, it is necessary to have specifically certified legal drafter to form the regulations. As in the principle of legal fiction, that person is considered to know the rule can be realized properly.